Use of Adverbials in Discussion Sections of Research Articles in Thai and International Journals - Malawaet, Napatrapee; Trakulkasemsuk, Wannapa (rEFLections, 2021)
The purpose of this study was to compare the discussion sections of research articles in applied linguistics in Thai and international journals. The corpus consisted of 20 English research articles: 10 from Thai journals and 10 from international journals. The adverbials framework of Biber et al. (1999) was employed in this study. The study explained the different usage of adverbials in discussion sections of both corpora. The results show that most of the use of adverbials in research article discussion sections in Thai and international journals is similar. There are five adverbials which are different and influence the presentation of content in discussion sections. It is hoped that this study may help teachers to design writing courses for novice writers or undergraduate and postgraduate students in writing research article discussion sections to publish in an international level.